KEWAJIBAN NOTARIS UNTUK MELEKATKAN LEMBARAN BERISI SIDIK JARI PENGHADAP PADA MINUTA AKTA BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - BARRORI MIRZA (PREMISE LAW JURNAL, 2016)
An authentic deed will become complete evidence when it is signed by stakeholders, based on Article 16, paragraph 1, point c of UUJN (Notarial Act). The implementation of attaching fingerprints of the persons appearing, based on Article 16, paragraph 1, point c of UUJN, was by using the thumb of right hand, and is attached in a separate piece of paper. If the person appearing does not attach his fingerprint, there should be a notification at the end of the deed which states that the person appearing does not attach his fingerprint, witnessed by witnesses and the Notary, and however, a Notary who does not apply Article 16, paragraph 1, point c of UUJN will get administrative sanction, this law by a) written warning, b) suspension, c) honorable discharge, and d) dishonorable discharge, it is also recommended that witnesses’ fingerprints should be attached, and the location of the fingerprints of the person appearing should be focused on a certain point. Keywords : Fingerprint, Deed Minute, Notarial Act